Repeat virological and serological profiles in hospitalized patients initially tested by nasopharyngeal RT‐PCR for SARS‐CoV‐2. Issue 12 (29th July 2021) - Reich, Noah; Lowe, Christopher F.; Puddicombe, David; Matic, Nancy; Greiner, Jesse; Simons, Janet; Leung, Victor; Chu, Terry; Naik, Hiten; Myles, Nick; Burns, Laura; Romney, Marc G.; et al.
Abstract: Real‐time polymerase chain reaction (PCR) for SARS‐CoV‐2 is the mainstay of COVID‐19 diagnosis, yet there are conflicting reports on its diagnostic performance. Wide ranges of false‐negative PCR tests have been reported depending on clinical presentation, the timing of testing, specimens tested, testing method, and reference standard used. We aimed to estimate the frequency of discordance between initial nasopharyngeal (NP) PCR and repeat NP sampling PCR and serology in acutely ill patients admitted to the hospital. Panel diagnosis of COVID‐19 infection is further utilized in discordance analysis. Included in the study were 160 patients initially tested by NP PCR with repeat NP sampling PCR and/or serology performed. The percent agreement between initial and repeat PCR was 96.7%, while the percent agreement between initial PCR and serology was 98.9%. There were 5 (3.1%) cases with discordance on repeat testing. After discordance analysis, 2 (1.4%) true cases tested negative on initial PCR. Using available diagnostic methods, discordance on repeat NP sampling PCR and/or serology is a rare occurrence.